Congenital Cataract and Its Genetics: The Era of Next-Generation Sequencing - Taylan Şekeroğlu, Hande (Turk J Ophthalmol, 2021)
Congenital cataract is a challenging ophthalmological disorder which can cause severe visual loss. It can be diagnosed at birth or during the first year of life. Early diagnosis and treatment are crucial for the visual prognosis. It can be associated with various ocular and systemic abnormalities. Determining whether congenital cataract is isolated or associated with other pathology is an indispensable step for the prediction of potential vision as well as early diagnosis and treatment of conditions that can cause morbidity or mortality. Many genes have been identified in the molecular etiology of congenital cataract. Most mutations have been reported in the crystallin genes. Determination of the genetic cause may not only enable individualized genetic counseling but also help to identify concomitant ocular and/or systemic disorders depending on the characteristics of the genetic test used. Recently, next-generation sequencing in particular has become an evolving technology for determining the molecular etiology of congenital cataract and furthering our knowledge of the disease.